Cardiovascular Disease in Bangladesh: A Review - Islam, AKM Monwarul; Mohibullah, AKM; Paul, Timir (Bangladesh Heart Journal, 2017)
Like elsewhere, cardiovascular disease (CVD) is an increasingly important cause of morbidity and mortality in Bangladesh. Over the past few decades, because of epidemiological transition, the prevailing disease pattern in this country changed from predominantly communicable to predominantly non- communicable disease, CVD contributes to the latter a lot. Actually, CVD particularly coronary artery disease (CAD) is getting epidemic proportion day by day. Hypertension and heart failure are on the rise, whereas the prevalence of acute rheumatic fever is declining. However, despite some efforts, reliable data concerning various aspects of CVD is inadequate at present. The current prevalence of hypertension, CAD, rheumatic fever and rheumatic heart disease and stroke may be 20-25%, 4-6%, <1/1000, 0.3- 1.0% respectively. Besides conventional risk factors for different CVD, genetic predisposition and some novel issues like high salt intake, arsenicosis, hypovitaminosis D and air pollution may play important role in the aetiopathogenesis of CVD in this population. Formulation of appropriate policy and more emphasis on preventive strategy may help combat CVD in Bangladesh. Bangladesh Heart Journal 2016; 31(2) : 80-99